2018
DOI: 10.1093/humrep/dex372
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis induces gut microbiota alterations in mice

Abstract: This research was supported by Grant (81571417) from the National Science Foundation of China and Grant (2015GSF118092) from the Technology Development Plan of Shandong Province. The authors report no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
134
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 57 publications
5
134
0
2
Order By: Relevance
“…Five of the eighteen studies identified were conducted using animal models. One study involved the use of rhesus monkeys as a non‐human primate model, whereas the remaining four studies used murine or rodent models . This included Sprague‐Dawley and C57BL models; however, one study did not declare which murine model was used .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of the eighteen studies identified were conducted using animal models. One study involved the use of rhesus monkeys as a non‐human primate model, whereas the remaining four studies used murine or rodent models . This included Sprague‐Dawley and C57BL models; however, one study did not declare which murine model was used .…”
Section: Resultsmentioning
confidence: 99%
“…One study involved the use of rhesus monkeys as a non‐human primate model, whereas the remaining four studies used murine or rodent models . This included Sprague‐Dawley and C57BL models; however, one study did not declare which murine model was used . Endometriosis was surgically induced in the murine/rodent models via intraperitoneal transplantation; however, there was slight variation among the methods used in each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations